2023
DOI: 10.1021/acs.est.2c09164
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Emission Reduction Requirements for China to Achieve World Health Organization Global Air Quality Guidelines

Abstract: A big gap exists between current air quality in China and the World Health Organization (WHO) global air quality guidelines (AQG) released in 2021. Previous studies on air pollution control have focused on emission reduction demand in China but ignored the influence of transboundary pollution, which has been proven to have a significant impact on air quality in China. Here, we develop an emission–concentration response surface model coupled with transboundary pollution to quantify the emission reduction demand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 64 publications
(101 reference statements)
0
9
0
Order By: Relevance
“…Emerging studies 38 , 46 , 47 indicated even stronger and steeper concentration-response functions at low PW PM 2.5 levels (<10 μg/m 3 ), further strengthening the greater benefits at reduced PM 2.5 exposure. However, future mitigation of PM 2.5 air pollution at lower PM 2.5 concentrations will be increasingly challenging, due to growing importance of aerosols arising from climate change (e.g., wildfire and dust) 32 , 36 , 48 , and as more readily mitigable anthropogenic sources are reduced 49 , 50 .…”
Section: Resultsmentioning
confidence: 99%
“…Emerging studies 38 , 46 , 47 indicated even stronger and steeper concentration-response functions at low PW PM 2.5 levels (<10 μg/m 3 ), further strengthening the greater benefits at reduced PM 2.5 exposure. However, future mitigation of PM 2.5 air pollution at lower PM 2.5 concentrations will be increasingly challenging, due to growing importance of aerosols arising from climate change (e.g., wildfire and dust) 32 , 36 , 48 , and as more readily mitigable anthropogenic sources are reduced 49 , 50 .…”
Section: Resultsmentioning
confidence: 99%
“…Electrostatic interaction between Pb 2+ and adsorbent can enhance collection of the positively charged Pb 2+ , which makes the Pb 2+ easy to recycle. [ 149–152 ] However, choice of suitable Pb adsorbents is challenging. Park et al.…”
Section: Research Progress Of Recycling and Reusingmentioning
confidence: 99%
“…Previous research indicates that in VOC-limited areas, O 3 concentrations may increase if NO x emission control is inadequate, particularly in urban areas. Therefore, the highly nonlinear relationship resulting from the complex interplay of atmospheric processes and precursor emissions in the O 3 chemistry makes it challenging to formulate effective NO x and VOCs control strategies to mitigate the effect of O 3 pollution. Some studies have emphasized the importance of VOCs control in the near future and the need for significant reductions in NO x emissions to effectively mitigate O 3 levels. ,, However, the unified emission control ratios of VOCs and NO x assumed at a regional or national and temporal scale overlook the variations between different cities and among different months and are limited in their practical application at the city level due to the existing methodological constraints. , Only a few studies have made progress in optimizing the pathways for NOx and VOCs control to achieve specific O 3 concentration targets such as the 90th maximum daily 8-h average (90th MDA8) by employing response surface models and marginal emission abatement cost curves. , Nevertheless, researches on the damage O 3 inflicts on human health demonstrate that the 90th MDA8 O 3 exposure is insufficient to clarify the O 3 health burden. The new World Health Organization global air quality guidelines released in 2021 directly points out the significance of mitigating peak season O 3 exposure to reduce long-term O 3 health impact .…”
Section: Introductionmentioning
confidence: 99%
“…29,31−33 Only a few studies have made progress in optimizing the pathways for NOx and VOCs control to achieve specific O 3 concentration targets such as the 90th maximum daily 8-h average (90th MDA8) by employing response surface models and marginal emission abatement cost curves. 34,35 Nevertheless, researches on the damage O 3 inflicts on human health demonstrate that the 90th MDA8 O 3 exposure is insufficient to clarify the O 3 health burden. The new World Health Organization global air quality guidelines released in 2021 directly points out the significance of mitigating peak season O 3 exposure to reduce long-term O 3 health impact.…”
Section: ■ Introductionmentioning
confidence: 99%